2015
DOI: 10.1103/physrevd.91.105033
|View full text |Cite
|
Sign up to set email alerts
|

Generalized soft breaking leverage for the MSSM

Abstract: In this work we study implications of additional non-holomorphic soft breaking terms (µ , A t , A b and A τ ) on the MSSM phenomenology. By respecting the existing bounds on the mass measurements and restrictions coming from certain B-decays, we probe reactions of the MSSM to these additional soft breaking terms. We provide examples in which some slightly excluded solutions of the MSSM can be made to be consistent with the current experimental results. During this, even after applying additional fine-tuning co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 107 publications
1
31
0
Order By: Relevance
“…All the above that restrict the MSSM parameter space may be addressed reasonably well when one includes non-holomorphic (NH) soft terms on the top of the usual holomorphic soft terms of MSSM [69,70]. Staying within an MSSM setup terms like φ 2 φ * or a higgsino mass term like ψψ can be soft SUSY breaking in nature if there is no presence of a gauge singlet field [71].…”
Section: Jhep01(2018)158mentioning
confidence: 99%
See 2 more Smart Citations
“…All the above that restrict the MSSM parameter space may be addressed reasonably well when one includes non-holomorphic (NH) soft terms on the top of the usual holomorphic soft terms of MSSM [69,70]. Staying within an MSSM setup terms like φ 2 φ * or a higgsino mass term like ψψ can be soft SUSY breaking in nature if there is no presence of a gauge singlet field [71].…”
Section: Jhep01(2018)158mentioning
confidence: 99%
“…Staying within an MSSM setup terms like φ 2 φ * or a higgsino mass term like ψψ can be soft SUSY breaking in nature if there is no presence of a gauge singlet field [71]. There have been several works over the past two decades [69][70][71][72][73][74][75][76][77][78][79][80][81][82] that analyzed the effects of introducing NH soft terms. 2 There are three distinct signatures i) the trilinear NH terms may enhance L-R mixing thus influencing various phenomenologies, ii) higgsinos get an additional soft-term source, iii) the Higgs potential remains unaffected at the tree level thus electroweak fine-tuning may hardly change.…”
Section: Jhep01(2018)158mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in refs. [33,34] that extension of the generic MSSM via the inclusion of non-holomorphic (NH) soft SUSY breaking terms, quite satisfactorily ameliorates all the above problems of the MSSM. This extended MSSM, namely the Non-Holomorphic MSSM (NHSSM) has the particle content identical to that of the MSSM, but have extra soft SUSY breaking terms.…”
Section: Jhep10(2017)154mentioning
confidence: 99%
“…It has been shown that in the absence of any gauge singlet it is possible to extend the SUSY breaking soft sector by including NH soft SUSY breaking terms, without aggravating any quadratic divergence [71,74,80]. Thus, the NH soft terms of the NHSSM in general that include trilinear coupling terms as well as a NH higgsino mass (µ ) term are given by [33,83] …”
Section: Ccb In Nhssmmentioning
confidence: 99%